Respuesta :
Ok so first we need to distribute so:
=(4)(b)+(4)(2)+−3b
=4b+8+−3b
So now that we've distrubuted that we are now going to Combine Like Terms:
=4b+8+−3b
=(4b+−3b)+(8)
Finally your answer is:
=b+8
I hope this helps you!
=(4)(b)+(4)(2)+−3b
=4b+8+−3b
So now that we've distrubuted that we are now going to Combine Like Terms:
=4b+8+−3b
=(4b+−3b)+(8)
Finally your answer is:
=b+8
I hope this helps you!
4 (b + 2 ) - 3b
....
Distribute 4 into the parenthesis.
......
We now have: 4b + 8 - 3b.
............
Time to combine like terms.
...................
Which gives us ---> 1b + 8
....
Distribute 4 into the parenthesis.
......
We now have: 4b + 8 - 3b.
............
Time to combine like terms.
...................
Which gives us ---> 1b + 8